Reel resistance the cinema of Jean-Marie Teno - Thackway, Melissa 1969-; Téno, Jean-Marie 1954- (James Currey, 2020)
Weaving together critical analysis and a filmic conversation, this book journeys through the multiple layers of Cameroonian filmmaker Jean-Marie Teno's thematically and aesthetically challenging body of work, framed here as a form of decolonial cinematic resistance
Title from publisher's bibliographic system (viewed on 22 Jul 2022)
Keywords: Téno, Jean-Marie; Téno, Jean-Marie -- 1954-; Motion pictures, African / Cameroon / History and criticism / 20th century; Motion picture producers and directors / Cameroon; Documentary films / Africa / History and criticism; Film; Filmografie